Maritime Operations and Emergency Preparedness in the Arctic–Competence Standards for Search and Rescue Operations Contingencies in Polar Waters - Schmied, Johannes; Borch, Odd Jarl; Kheiri Pileh Roud, Ensieh; Fjørtoft, Kay Endre; Selvik, Ørjan; Berg, Tor Einar; Parsons, James R. (2017)
Emergencies on large passenger ships in the remote High North may lead to a mass rescue operation with a heavy strain on the emergency preparedness systems of the Arctic countries. This study focuses on the need for competencies related to large-scale Search and Rescue operations (SAR operations) amongst the shipping companies, vessels and governments involved. A SAR operation is the activity related to finding and rescuing people in distress. Several international standards, in particular the conventions by the International Maritime Organization (IMO), provide direction for education and training of seafarers and rescue staff. This study elaborates on the operational competence requirements for key personnel involved in large scale SAR operations. Findings from real SAR incidents and exercises provide in-depth understanding on the operational challenges. The chapter gives directions for competence programs, beyond obligatory international standards, and recommendations for further research.